The budding yeast Polo-like kinase Cdc5 is released from the nucleus during anaphase for timely mitotic exit - Botchkarev, Vladimir V (Cell Cycle, 2014)
Polo-like kinases are important regulators of multiple mitotic events; however, how Polo-like kinases are spatially and temporally regulated to perform their many tasks is not well understood. Here, we examined the subcellular localization of the budding yeast Polo-like kinase Cdc5 using a functional Cdc5-GFP protein expressed from the endogenous locus. In addition to the well-described localization of Cdc5 at the spindle pole bodies (SPBs) and the bud neck, we found that Cdc5-GFP accumulates in the nucleus in early mitosis but is released to the cytoplasm in late mitosis in a manner dependent on the Cdc14 phosphatase. This Cdc5 release from the nucleus is important for mitotic exit because artificial sequestration of Cdc5 in the nucleus by addition of a strong nuclear localization signal (NLS) resulted in mitotic exit defects. We identified a key cytoplasmic target of Cdc5 as Bfa1, an inhibitor of mitotic exit. Our study revealed a novel layer of Cdc5 regulation and suggests the existence of a possible coordination between Cdc5 and Cdc14 activity.